People’s names in contemporary Polish (based on the material from the University of Warsaw Language Observatory) - Senderska, Joanna (Papers in Linguistics, 2021)
The aim of the article is to analyse people’s names in order to point out the most noticeable tendencies enriching Polish vocabulary, i.e. creating and borrowing new lexical items or only their meanings from other languages. The source material was excerpted from the website of the University of Warsaw Language Observatory (Obserwatorium Językowe Uniwersytetu Warszawskiego), where the newest Polish lexis is registered. There are about 690 people’s names, an overwhelming majority of them (about 630) being lexical neologisms, i.e. new derivatives, compounds, loan words and loan translations. The remaining lexical items are semantic neologisms (with new meanings assigned to existing lexical items) and phraseological neologisms (new idioms and phraseological calques). The scrutiny of excerpted neologisms confirms that English still has a strong influence on contemporary Polish, not only in terms of lexis but also in terms of the derivational system.